Health-related quality of life - Hackshaw, Allan (Henry Stewart Talks, 2025)
Measuring quality of life, Short-Form 12 (SF-12) and the Dermatology Life Quality Index questionnaire, Self-reporting quality of life, Global health score, Analysing and interpreting quality of life